2023
DOI: 10.1371/journal.pone.0274586
|View full text |Cite
|
Sign up to set email alerts
|

Artificial diet alters activity and rest patterns in the olive fruit fly

Abstract: Olive fruit flies, Bactrocera oleae (Diptera: Tephritidae) reared in the laboratory on an artificial diet are essential for the genetic control techniques against this pest. However, the colony’s laboratory adaptation can affect the quality of the reared flies. We used the Locomotor Activity Monitor to track the activity and rest patterns of adult olive fruit flies reared as immatures in olives (F2-F3 generation) and in artificial diet (>300 generations). Counts of beam breaks caused by the adult fly activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Male C. capitata that courted but did not mate have a similar lifespan to those that courted and then mated, meaning that courtship alone is metabolically costly [50]. It was also found that mating decreased the locomotor activity levels of males; these findings provide evidence that both courting and mating are metabolically costly [36]. Males may need to compete for access to mates or invest in courtship displays.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Male C. capitata that courted but did not mate have a similar lifespan to those that courted and then mated, meaning that courtship alone is metabolically costly [50]. It was also found that mating decreased the locomotor activity levels of males; these findings provide evidence that both courting and mating are metabolically costly [36]. Males may need to compete for access to mates or invest in courtship displays.…”
Section: Discussionmentioning
confidence: 81%
“…Flies that had been kept with conspecifics of the opposite sex were monitored by a human observer to verify mating. We observed the flies for mating from 16:00 to 21:00 because, in this species, mate searching and courtship take place during the late evening [34,36]. Individuals that had not mated were removed from the experiment and were replaced with others that had mated.…”
Section: Experimental Procedures and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, we pooled the recordings from the three monitors to obtain the total activity, which represented the cumulative movements across all three monitors (a total of 1440 recordings: 840 during the daytime and 600 during the nighttime). Next, we calculated the mean value for each individual adult every two hours, following the approach described by Terzidou et al [7]. Based on these results, we constructed twelve radar diagrams per age group and type of stress.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…Recent studies were conducted on B. oleae regarding the lifecycle [5] and how landscape affects insect movement [6]. Additionally, the difference in mobility between wild olive fruit flies and artificially reared insects was studied using a LAM25 system (locomotor activity monitor)-Trikinetics [7]. It would be very useful to expand such studies to the adults of B. oleae to investigate the effects of abiotic stress conditions such as food and water deprivation.…”
Section: Introductionmentioning
confidence: 99%